A traditional secret saving method of woven designs in talapatra pothi by Rangani at Dhalapathar - Iswar Chandra Nayak
A traditional secret saving method of woven designs in talaptra pothi (palm leaf manuscripts) by a Buddhist weaving community Rangani at Dhalapathar has been discussed. It describes the way of representing woven designs numerically in an unconventional way to make incomprehensible for others. The novelty of this method is to prevent other weaving communities of the state from purloining of their original designs which is rare and hardly seen anywhere in India.